RANCANG BANGUN APLIKASI PENENTUAN KELAYAKAN PEMBERIAN KREDIT MENGUNAKAN METODE FUZZY LOGIC PADA ARD MOTOR - Rafsanjani, M. Ali Akbar; Sudarmaningtyas, Pantjawati; Sulistiowati, Sulistiowati (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2015)
Ard Motor is a company engaged in the sale of car spare parts. The company offers customers two ways of payment are cash payments and loan payments. In the process of granting credit, the company assesses the credit worthiness from the customer’s debt, the amount of credit purchases will be proposed, and the business value. But the problem for the company is many customers are already overdue its payment. This is due partly intentional factor customers in payment. Besides making lending decisions are subjective only give a decision worthy or not.Overcoming these problem, therefor the application to determine credit worthiness was made. The parameter that used is the number of purchase transactions, the amount of debt, purchase frequency and value of character to assess the customer, In order for credit granting ratings become not subjective therefor in this application fuzzy logic methods are used to support the decissions. The results from evaluation it can be concluded that the application can generate a percentage value of credit worthiness so it can be more accurate, and the application can determine the priority lending who was worthy so that companies can provide credit payment to the right customers.Keywords : Credit, Feasibility Assessment of Credit Applications, Fuzzy Logic